A broadband perfect metamaterial absorber with angle-insensitive characteristics. Issue 3 (11th February 2023) - Liang, Cang; Kong, Xianglin; Wang, Fengjun; Xu, Ruofeng; Fu, Yixiang; Pang, Xiaoyu; Zhang, Shengjun; Shen, Xiaopeng; Zhao, Lei
Abstract : A broadband perfect metamaterial absorber (MA) based on bilayer resistive films with different structure units is proposed in the microwave regime. An equivalent circuit model based on transmission line theory is established to guide the absorber design and explain its broadband and perfect absorption mechanism. The absorber characters high absorptivity and stable angular. The MA displays more than 98% absorption from 4.9 to 22.6 GHz at normal incidence. The performance is suitable for transverse electric (TE) and transverse magnetic (TM) waves at normal incidence, while absorption is better than 90% (80%) within the oblique incidence 50° (60°). The measured results of absorption and 10 dB radar cross section (RCS) agree well with the simulated ones.